Kejahatan Bullying terhadap Siswa Sekolah Dasar Jiyu 2 Mojokerto dalam Tinjauan Kriminologi - Imroatin Arsali; Intan Kartika Sari (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2023)
Nowadays, children's character education is starting to experience erosion, resulting in many criminal behaviors being considered normal, such as bullying, which often occurs in educational environments. Elementary schools as a place to gain knowledge cannot necessarily guarantee healthy social interactions, for example, as happened at the Jiyu 2 Mojokerto State Elementary School where the bullying activities that occurred there were considered a normal form of interaction between students. Referring to this phenomenon, this research aims to find out how the criminology review includes victims, perpetrators, crimes, and responses from the community related to bullying against elementary school students in the case study of SDN Jiyu 2 Mojokerto. This research was conducted empirically qualitatively with a juridical and sociological approach through collecting primary data originating from field observations with interviews and questionnaires as well as secondary data originating from literature studies in the form of books, journals, articles and theses. From the research results, it was concluded that the classification of bullying problems that occurred at SDN Jiyu 2 Mojokerto was mostly in the form of verbal bullying which was mostly carried out by peers. self.